Measuring the financial sustainability and its influential factors in local governments. - Navarro Galera, Andrés; Rodríguez Bolívar, Manuel Pedro; Alcaide Muñoz, Laura; López-Subires, María Deseada (Taylor & Francis, 2016)
The economic crisis has led international organizations and previous research to point out the need for measuring and controlling financial sustainability in governments. Based on the main international pronouncements, this article seeks to contribute to the measurement and management of the financial sustainability, analysing the income statement evolution and identifying its influential factors. An empirical study of Spanish municipalities is then undertaken to test the relationship between the measure of the financial sustainability and three dimensions proposed by International Federation of Accountants (IFAC) (revenues, debt and services). Our findings indicate that the income statement is a good approach for the financial sustainability assessment, because it reveals relevant information about its three dimensions, allowing to identify the specific factors which could provoke sustainability problems on public services.
https://openpolicyfinder.jisc.ac.uk/id/publication/4942
Keywords: Administración local - Aspectos económicos; Financial sustainability; Local government; Income statement